2010
DOI: 10.1186/1756-0500-3-169
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asymptomatic bacteriuria in type 2 diabetic subjects with and without microalbuminuria

Abstract: BackgroundDiabetic subjects, especially women, show high prevalence of asymptomatic bacteriuria (ASB). The aim of the present study was to evaluate the prevalence of ASB in subjects with type 2 diabetes mellitus (T2D) with and without microalbuminuria (MA).FindingsA hundred diabetic subjects with MA (53 males/47 females, mean age ± standard deviation: 65.5 ± 11.1 years) and 100 diabetic subjects without MA (52 males/48 females, mean age ± standard deviation: 65.4 ± 11.3 years), consecutively attending the outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 25 publications
(38 reference statements)
1
26
0
1
Order By: Relevance
“…Regarding symptoms, five studies evaluated only asymptomatic bacteriuria [4,5,7,11,12], one study evaluated asymptomatic plus symptomatic [6], and one study did not report frequency of symptoms [13]. The chance for microalbuminuria or macroalbuminuria was not increased by the presence of bacteriuria in a sensitivity analysis including only studies that evaluated asymptomatic bacteriuria (OR: 1.71, 95% CI: 0.89–3.30, I 2 = 71.7%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding symptoms, five studies evaluated only asymptomatic bacteriuria [4,5,7,11,12], one study evaluated asymptomatic plus symptomatic [6], and one study did not report frequency of symptoms [13]. The chance for microalbuminuria or macroalbuminuria was not increased by the presence of bacteriuria in a sensitivity analysis including only studies that evaluated asymptomatic bacteriuria (OR: 1.71, 95% CI: 0.89–3.30, I 2 = 71.7%).…”
Section: Resultsmentioning
confidence: 99%
“…However, the possible association between bacteriuria and increased urinary albumin is controversial. Some cross-sectional studies observed an increased prevalence of macroalbuminuria and/or microalbuminuria in patients with bacteriuria [4,5], while other studies do not support this observation [6,7]. The aim of the present study was to investigate the association of albuminuria and bacteriuria in patients with type 2 diabetes by a systematic review and meta-analysis of observational studies.…”
Section: Introductionmentioning
confidence: 99%
“…mirabilis is the most common pathogen of the urinary tract that is more common in complicated urinary tract infections, particularly in catheter-associated UTI (CAUTI) that causes about 10-44% of long-term CAUTIs [18,2]. Evidence shows that urease, hemolysin, and Pta are considered as the most important virulence factors of this uropathogen which has been involved in the urinary tract injuries in the suffering patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…P. mirabilis can cause different forms of UTI including cystitis, pyelonephritis, asymptomatic bacteriuria, bacteremia, urolithiasis and progression to potentially life-threatening urosepsis [2,3]. According to the previous studies, P. mirabilis causes between 1-10% of all urinary tract infections and is the cause of 11 million physician visits and $3.5 billion dollars medical costs in the United States [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation